The experimental investigation of drawing parameters on the deep drawing of Al1050 sheets in angular deep-drawing dies - Savas, V.; Ozay, C.; Aytac, F. (Natl Inst Optoelectronics, 2015)
The deep drawing process of sheet plate takes an important place in metal forming. The drawing ratios with traditional deep-drawing dies used in industry are limited. In order to obtain optimal process parameters, the geometries of die/blank holder and punch radiuses are particularly important factors. In this study, we investigated the effects of blank holder and die shapes for Al1050 sheet metal. We measured the distribution of blank holder force (BHF), forming load at different drawing depths as well as thickness reduction of cup wall thickness for each set of matrix and blank holder geometries. The experimental implementation has shown that the angular dies are effective way to promote deep drawability of Al1050. Deep drawing ratios with matrix/blank holder angle designed have been increased about 10 % larger than those that usually can be obtained by a conventional die.
Keywords: Limit drawing ratio (LDR); Deep drawing; Al1050; Angular deep drawing die